The Influence of Slimming Products on Women's Sex Hormones, Oxidative Stress, and Immune Systems in Diwaniyah City.: Pengaruh Produk Pelangsing terhadap Hormon Seksual, Stres Oksidatif, dan Sistem Kekebalan Tubuh Wanita di Kota Diwaniyah. - Meaad Nasser Hussein (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The use of fat burner supplements has increased alongside concerns about metabolic and physiological risks. Specific Background This study examines biochemical and hormonal responses associated with fat burner compounds, particularly focusing on oxidative stress and inflammatory markers. Knowledge Gap Limited research has integrated oxidative stress biomarkers with hormonal and inflammatory responses in the context of fat burner exposure. Aims This study aims to analyze the relationship between fat burner use, oxidative stress indicators, and hormonal changes. Results The findings indicate alterations in oxidative markers, inflammatory cytokines, and lipid metabolism, suggesting a complex physiological response linked to supplement use. Novelty The study provides a combined evaluation of oxidative stress, hormonal activity, and inflammatory biomarkers within a single analytical framework. Implications The results highlight potential health risks and provide a basis for further clinical and biochemical investigations into supplement-related metabolic changes. Keywords: Oxidative Stress, Fat Burners, Biomarkers, Inflammation, Metabolic Changes Key Findings Highlights Altered antioxidant and oxidant balance observed in subjects Cytokine activity associated with metabolic disturbance Hormonal variation linked to physiological stress responses